Detection and confirmation of zilpaterol in equine hair using liquid chromatography–mass spectrometry. Issue 1 (21st August 2021) - Moeller, Benjamin C.; Clifford, Amel; Emery, Richard T.; Alarcio, Gwen; Favro, Gianna; Arthur, Rick M.
Abstract: Zilpaterol is a β2 ‐adrenergic agonist and a repartitioning agent that has a high potential for abuse in equine performance athletes. Analysis of zilpaterol in hair is an alternative sampling matrix that extends detection time periods beyond those found in urine or blood samples. Our laboratory has been screening for zilpaterol in hair for many years and recently detected and confirmed its presence in official samples. Accordingly, a liquid chromatography–mass spectrometry method was developed and validated to detect and confirm zilpaterol in equine hair. Briefly, equine hair was decontaminated, cut, and pulverized prior to disruption and liquid–liquid extraction in basic conditions. Following extraction, the sample was introduced to an Agilent 1260 HPLC and zilpaterol was separated using a reverse phase gradient with a total run time of 12.5 min. Following chromatographic separation, zilpaterol and its corresponding stable isotope labeled internal standard were introduced via positive mode electrospray ionization to a Thermo Q‐Exactive Plus mass spectrometer and spectra collected using parallel reaction monitoring. The methodology was validated using in‐house criteria including characterization of accuracy, precision, recovery, linear range, matrix effects, limit of detection, and limit of quantitation, and the method was found to be fit‐for‐purpose to confirm the presence of zilpaterol in equine hair. This methodology has been used to detect and confirm the presence of zilpaterol from out‐of‐competition hair samples submitted by regional racing authorities. Abstract : An LC‐MS method to detect and confirm the presence of zilpaterol in equine hair was developed and validated. This methodology has been used to detect and confirm the presence of zilpaterol from out‐of‐competition hair samples submitted by regional racing.